2022
DOI: 10.3389/fpsyg.2022.938116
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the links between alexithymia and cognitive emotion regulation strategies in internet addiction: A network analysis model

Abstract: Alexithymia and emotion regulation are closely related to internet addiction. However, no research has examined how the different components of alexithymia are associated with cognitive emotion regulation in the context of multi-strategy use in internet addiction. The current study aimed to investigate the relation between alexithymia and cognitive emotion regulation in individuals with internet addiction via network analysis. Participants included 560 students with Young’s Internet Addiction Test scores great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
(87 reference statements)
2
3
0
Order By: Relevance
“…This further confirms the necessity for clinical healthcare professionals to intervene in these core symptoms, as they hold crucial positions within the network. The present study identified "DIF" and "DDF" as the strongest edge connections within the alexithymia cluster, which is consistent with findings from previous network analyses in adolescent populations (49,50). Notably, "DIF" emerged as the most predictable and strongest node in the network.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This further confirms the necessity for clinical healthcare professionals to intervene in these core symptoms, as they hold crucial positions within the network. The present study identified "DIF" and "DDF" as the strongest edge connections within the alexithymia cluster, which is consistent with findings from previous network analyses in adolescent populations (49,50). Notably, "DIF" emerged as the most predictable and strongest node in the network.…”
Section: Discussionsupporting
confidence: 92%
“…The present study identified “DIF” and “DDF” as the strongest edge connections within the alexithymia cluster, which is consistent with findings from previous network analyses in adolescent populations ( 49 , 50 ). Notably, “DIF” emerged as the most predictable and strongest node in the network.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some other researchers explained this difference from the perspective of attribution style. It is suggested that boys use more external attribution (e.g., blaming others) in adverse events; in contrast, girls use more internal attribution (e.g., selfblame) [67][68][69] and may further develop into internalizing problems under adversities [34]. In addition, some researchers pointed out that the social standards are stricter for girls in traditional Chinese culture [70].…”
Section: Effects Of Aces On Adolescents' Depression and Anxiety Sympt...mentioning
confidence: 99%
“…Cognitive strategies are a way for individuals to view and understand emotional events and can significantly affect their emotional and behavioral responses (Chawla and Ostafin, 2007;Zhang, 2020). Studies have confirmed that adolescents' coping strategies for emotional events gradually shift from external behavioral orientation to internal cognitive orientation (Luo et al, 2010;Xu, 2014). As a cognitive coping strategy, rumination plays an important role in adolescents' cognitive evaluation and behavioral response to peer victimization.…”
Section: The Moderating Role Of Rumination Tendencymentioning
confidence: 99%